SUSTAINABLE TOURISM DAN TRANSFORMASI PENDAPATAN EKONOMI LOKAL DI DESA WISATA BONJERUK LOMBOK TENGAH - Eka Saefan Rukzam (Journal of Innovation Research and Knowledge, 2026)
This study analyzes the role of sustainable tourism in transforming local community income in Desa Wisata Bonjeruk. The development of tourism villages has become an important strategy for improving community welfare while preserving local culture and environmental sustainability. This research aims to examine how sustainable tourism influences local economic transformation and community income patterns in Bonjeruk Tourism Village. This study uses a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving tourism village managers, local government representatives, tourism business actors, community leaders, and local residents participating in tourism activities. Data analysis employed the interactive model of Miles, Huberman, and Saldaña, including data reduction, data presentation, and conclusion drawing. The findings show that sustainable tourism has positively contributed to local economic transformation by creating new business opportunities such as homestays, culinary services, tour guiding, handicrafts, and other creative economic activities. Tourism development also generated multiplier effects that strengthened local economic activities. However, challenges remain regarding unequal economic access, infrastructure limitations, and dependence on tourist arrivals. This study highlights the importance of community participation and local cultural preservation in supporting sustainable tourism development and long-term local economic sustainability.